Pterygoid processes and synchondrosis spheno-occipital in the Rapid Maxillary Expansión - Chávez-Sevillano, Manuel (2015)
The Rapid Maxillary Expansion that involves the opening of the median palatine suture is used frequently to correct narrow arch maxillary and since the maxillary relates also with the skull base, the objective of this paper was to search in the literature the effects that the Rapid Maxillary Expansion produces on the pterygoid process and the spheno-occipital synchondrosis; analyzed clinically, with compute tomography, bone scintigraphy, cephalometric X-ray and the finite element method. The literature review was done on the data bases: Medline (PubMed), Scopus, Scielo, BSV (Bireme), ISI (Web of Sciencie) and Lilacs. It can be said that the forces it proportionate during the Rapid Maxillary Expansion not only to performs on the median palatine suture, but also on the pterygoid processes and even on the spheno-occipital synchondrosis, to making displacements and different concentrations of stress.